Influence of new complete dentures on the touch perception threshold and quality of life of edentulous patients - Penitente, Paulo Augusto [UNESP] (2024)
Objective: To evaluate the touch perception threshold of the alveolar mucosa and quality of life of edentulous patients before (T0) and 30 days after (T1) the insertion of new complete dentures. Background: Touch perception is important so that edentulous patients can detect the position of complete dentures in their mouth. Materials and methods: This study included 32 complete denture wearers with good oral and systemic health and no temporomandibular disorders for at least 5 years. At each time point (T0 and T1), two tests were performed (touch perception threshold and quality-of-life scale). The touch perception threshold (Von Frey or Semmes–Weinstein test) was assessed using nylon monofilaments on the regions of the alveolar mucosa of the maxilla and mandible. The Oral Health Impact Profile for edentulous individuals (OHIP-EDENT) was administered to evaluate oral health-related quality of life. Results: In the maxilla and mandible, the touch perception thresholds for all regions of the alveolar mucosa were significantly lower at T1 than at T0. The OHIP-EDENT mean scores showed that the overall quality of life was significantly better at T1 (3.6) than at T0 (4.7), and a significant improvement in quality of life was observed in all domains of the OHIP-EDENT at T1. For touch perception threshold, effect sizes ranged from 0.4 to 0.8; and for quality of life, effect sizes ranged from 0.4 to 1.0. Conclusions: New complete dentures reduced the touch perception threshold of the alveolar mucosa of both edentulous arches and improved individuals' quality of life.